Phytochemical Screening, Essential Metals Analysis and in vitro Anti-oxidation Activity of Rhus Tripartita Plant Roots (Journal of Humanitarian and Applied Sciences, 2023)
Phytochemical screening of Rhus Tripartita roots extract revealed presence of flavonoids, phenols, glycosides, diterpenes, carbohydrates, phytosterols, quinones and anthraquinones. All these organic classes are well known for their biological activity and this explains the use of this plant in folk medicine. Essential metals nutrients (Li, Na, K, Ca and Ba) levels were also determined. Potassium element concentration was the highest (0.789%) while Lithium element level was the lowest (0.003%). Anti-oxidation activity was performed by DPPH (1,1 diphenyl-2-picryl hydrazyl) radical scavenging method, the alcoholic extract of studied plant showed strong anti-oxidation activity comparing to the reference ascorbic acid, with IC50 values of 10.78 µg/ml and 13.49 µg/ml, respectively. The strong antioxidant activity of ethanol extract may be attributed to the presence of anti-oxidants phytochemicals such as flavonoids and phenols and phytosterols.
Keywords: Rhus Tripartita; Phytochemical screening; Antioxidants; DPPH; Essential elements